Position of Authority and Responsibility of Foundation Organs According to Law No. 28 of 2004 Concerning Foundations - Gunawan Gunawan; Endang Suprapti; Tihadanah Tihadanah (International Journal of Law, Crime and Justice, 2024)
This study analyzes the authority and responsibility of foundation organs as regulated in Law No. 28 of 2004 concerning Foundations in Indonesia. Foundations as non-profit legal entities play a central role in playing various social, educational, and humanitarian aspects in this country. Due to their crucial role, a comprehensive understanding of the position and responsibility of foundation organs is essential. The results of this study are expected to provide a deeper understanding of the role played by foundations in Indonesian society and their significant contribution to national development efforts. In addition, this study also has the potential to provide valuable input for improving regulations related to foundations in the future.